On the Freetown Waterfront: Household Income and Informal Wage Labour in a Nineteenth Century Port City - Laura Channing; Bronwen Everill (African Economic History Network (AEHN), 2020)
In this article, we use the 1831 Freetown Census alongside a variety of business and colonial papers to argue for the importance of informal, seasonal, flexible labor conducted at the household level - rather than individual breadwinner - in understanding how the economy in urban port cities in Africa and elsewhere in the Atlantic World operated in the nineteenth century. We construct a welfare ratio of different wage categories over the nineteenth century, as well as presenting sample household welfare ratios using real households from the Census. We argue that the flexibility, 'Ëœentrepreneurship', and precarity of the informal port city economy of the nineteenth century is relevant for understanding the nature of the modern gig economy and the predominance of 'Ëœunderemployment' and informal employment in African urban areas. An archivally-based long view of how households strategized about their welfare can help to undo some of the 'Ëœcompression of history' prevalent in the literature, and can offer contextualization to recent comparative real wage.
Keywords: N17; N37; 330; Standard of living; port city; household economy; Africa; informal economy